Transformasi Struktural di Jawa Timur : Pengaruh Pertumbuhan Ekonomi Sektoral terhadap Kemiskinan - Abdul Khafidzin; Nurul Istifadah (Trunojoyo University of Madura, 2020)
Sectoral economic growth affects the level of poverty in the area. High economic growth does not merely reduce poverty. Equitable distribution of income is also a matter that needs to be considered in line with increased economic growth. High economic growth is the process of accumulation of sectoral economic growth that has undergone a structural shift in its journey. Changes in economic structure are marked by a decrease in the contribution of the agricultural sector and an increase in the contribution of the industrial sector, both in gross domestic product (GDP) and in employment. Economic growth needs to be directed towards economic sectors that are effective in reducing poverty and creating equitable distribution of income. The purpose of this study is to answer the question of how the influence of sectoral economic growth on poverty in East Java. For this purpose the panel data regression model is used. The selection of variables is based on research objectives. Agriculture sector GRDP (VP), industrial sector GRDP (VI) and service sector GRDP (VJ) represent sectoral economic growth. The results of the test show an increase in the contribution of the industrial sector effectively reduces poverty. In other words, between the agriculture, industry and services sectors, only the industrial sector has positive and significant parameters for poverty in East Java.